2018
DOI: 10.1111/echo.13831
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic mitral valve thrombosis, malfunction, and paroxysmal mitral regurgitation

Abstract: Intermittent dysfunction of mechanical mitral valve prosthesis is an uncommon condition. It carries serious clinical implications if unrecognized. Here, we present a case of a 28-year-old female with a history of rheumatic multivalvular disease, for which she had undergone double valve replacement and tricuspid annuloplasty. Six months later, she presented with heart failure. Clinical examination revealed intermittent loss of closing clicks followed by a pansystolic murmur at the apex, suggestive of mitral pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…At 5 years postoperatively, we found a cumulative mortality rate of 17.0% after mitral valve repair and 24.9% after replacement. Although our results demonstrate time‐independent hazards, mortality in the replacement group may be driven by greater acute and subacute postoperative complications in the replacement group, such as a higher likelihood of atrioventricular groove disruption, 22,23 paravalvular leakage, 24,25 and valve thrombosis 26 in mitral valve replacement. In long‐term survival studies, Silaschi et al 7 found a 5‐year survival benefit of mitral valve repair over replacement in elderly patients in both unadjusted analyses (74.2% vs. 61.0%, p < 0.01) and in adjusted analyses (76.9% vs. 58.6%, p = 0.03), respectively.…”
Section: Commentmentioning
confidence: 58%
“…At 5 years postoperatively, we found a cumulative mortality rate of 17.0% after mitral valve repair and 24.9% after replacement. Although our results demonstrate time‐independent hazards, mortality in the replacement group may be driven by greater acute and subacute postoperative complications in the replacement group, such as a higher likelihood of atrioventricular groove disruption, 22,23 paravalvular leakage, 24,25 and valve thrombosis 26 in mitral valve replacement. In long‐term survival studies, Silaschi et al 7 found a 5‐year survival benefit of mitral valve repair over replacement in elderly patients in both unadjusted analyses (74.2% vs. 61.0%, p < 0.01) and in adjusted analyses (76.9% vs. 58.6%, p = 0.03), respectively.…”
Section: Commentmentioning
confidence: 58%
“…Intermittent malfunction is a rare but potentially serious complication of PHV replacement . It may be observed in both mitral and aortic valve prosthesis and may lead to either paroxysmal obstruction or regurgitation, depending on the valve location and on the phase of the cardiac cycle during which the leaflet is entrapped. The most frequently encountered causes of intermittent valve malfunction are pannus formation, prosthetic valve thrombosis, vegetations, remnants of subvalvular apparatus such as chordae tendineae and suture material .…”
Section: Case Presentationmentioning
confidence: 99%
“… 6 , 7 The most frequently reported causes of intermittent disk dysfunction include pannus formation, entrapment of the disk by thrombi (nonobstructive or obstructive), subvalvular mitral tissue, suture material, vegetations, ventricular myocardium, and arrhythmia. 4 , 5 , 8 , 9 A multimodality approach that includes transthoracic echocardiography (TTE), 2-dimensional (2D) or real-time 3-dimensional (RT-3D) transesophageal echocardiography (TEE), cardiac computed tomography (CT), and fluoroscopy may help the diagnosis of intermittent malfunction of the PHV. 10 If not treated appropriately, intermittent dysfunction can lead to permanent disc immobilization and have more catastrophic consequences.…”
Section: Introductionmentioning
confidence: 99%